Closer ties forged between UMP-UMRAH - Mohd. Zaki, Ahmad
Some 500 people attended the Casual Cultural Night 2 that saw performances staged by undergraduates from Universiti Malaysia Pahang (UMP) and Universitas Maritim Raja Ali Haji (UMRAH) from Riau, Indonesia.